Unlocking Purchase Preferences: Harnessing Psychographic Segmentation, Promotion and Location Strategies - Miko Andi Wardana; Adi Masliardi; Nur Afifah; Mohamad Sajili; Hasti Pramesti Kusnara (SAFE-Network, 2023)
This research examines the impact of Psychographic Segmentation, Promotion, and Location on consumers' Purchase Decisions. Data were collected through an online questionnaire distributed to 90 respondents who had visited hotels in Denpasar, Bali. Statistical techniques such as validity and reliability tests, correlation analysis, and multiple regression analysis were employed for data analysis. The findings indicate that Psychographic Segmentation significantly influences Purchase Decisions. Categorizing buyers based on psychological traits, lifestyle, and values plays a crucial role in shaping consumer preferences and motivations. Promotion also has a significant impact on Purchase Decisions, as effective promotional strategies create awareness and persuade target customers. Additionally, the Location of a business emerges as a critical factor, with strategic placement influencing customers' buying decisions. The regression analysis reveals that Psychographic Segmentation, Promotion, and Location collectively explain approximately 75.1% of the variance in Purchase Decisions. However, it is important to note that factors beyond the study's scope, such as product quality, pricing, brand reputation, and customer service, may also influence purchase decisions. These insights provide valuable guidance for businesses in developing targeted marketing strategies to enhance their competitive advantage. Understanding consumers' psychographic profiles, implementing effective promotions, and strategically locating operations can significantly influence Purchase Decisions, leading to increased sales and overall business success. Future research could explore additional variables to gain a more comprehensive understanding of consumer behavior in purchase decisions.